Alpaca herders: Vulnerability, adaptability and sensitivity to climate change - Barrantes Campos, Cecilio Antonio (2021)
The objective of this study was to develop an index of vulnerability of alpaca herders (VAH), based on the adaptive capacity index (ACI) and sensitivity (SI) to climate change herders. The study was carried out in 2014 obtaining information from 17 alpaca farms from five annexes of the Sallca Santa Ana Peasant Community (SSAPC), Huancavelica, Peru. A conceptual model of ACI and SI was generated, assigning weights and function values to sources and attributes. For this, an Expert Panel from La Molina National Agrarian University (UNALM) and Nexus Program of the Fulbrigth Commission, USA, was formed. The ACI was estimated from human, physical, financial, information and diversity resources. The SI with livelihood and grassland resources. The VAH was estimated with the combination of ACI and SI, using fuzzy logic obtaining three categories: low, moderate and high. The U Mann-Whitney test contrasted 31 attributes of ACI and SI among the VAH categories. The 58.8% of SSAPC alpaca farms have low (0.2986 ± 0.0134) and 41.2% moderate (0.3800 ± 0.0069) of ACI. The 52.9% of alpaca farms have high (0.5863 ± 0.0277), 35.3% moderate (0.4053 ± 0.0122) and 11.8% low (0.2994 ± 0.0107) of SI. The 76.5% of alpaca farms have moderate (0.4390 ± 0.0208) and 23.5% high (0.6605 ± 0.0266) of VAH. The attributes of head of household and presence of sheds differed significantly between ACI categories (p<0.15). The attributes grassland trend (p<0.01), migrant contribution and vegetation diversity (p<0.10) and grassland condition (p<0.15) differed significantly between SI categories. The VAH revealed that the alpaca farms with high vulnerability correspond to a high SI (>0.47) and low ACI (<0.35). Instead, the alpaca farms with moderate vulnerability present an ACI and SI moderate (0.35-0.47). Both cases are adjusted to the results of other vulnerability indices at the producer level.